An efficient total synthesis of leukotriene B4 - Primdahl, Karoline Gangestad; Tungen, Jorn Eivind; Aursnes, Marius; Hansen, Trond Vidar; Vik, Anders (Organic & biomolecular chemistry, 2015)
Lipid mediators have attracted great interest from scientists within the chemical, medicinal, and pharmaceutical research community. One such example is leukotriene B-4 which has been the subject of many pharmacological studies. Herein, we report a convergent and stereoselective synthesis of this potent lipid mediator in 5% yield over 10 steps in the longest linear sequence from commercial starting materials. The key steps were a stereocontrolled acetate-aldol reaction with Nagao's chiral auxiliary and a Z-selective Boland reduction. All spectroscopic data were in agreement with those previously reported.